Supreme whispers: conversations with judges of the supreme court of India 1980-1989 - Chandrachud, Abhinav (Gurgaon, 2018)
In 1980, a brilliant young American scholar, George H. Gadbois, Jr. , met five judges of the Supreme Court of India.
Keywords: "Judges of the Supreme Court, India"